Correlative Dark-Field and Photoluminescence Spectroscopy of Individual Plasmon-Molecule Hybrid Nanostructures in a Strong Coupling Regime - Herrera-Urbina, F (American Chemical Society, 2019)
Light-matter interactions play a crucial role in several prominent nano-optical phenomena, such as plasmon-mediated fluorescence, nanoscale lasing, and strong plasmon-exciton coupling. The latter holds promise for the development of nanoscale nonlinear optical schemes and room-temperature polaritonic lasers. In recent years, strong coupling in nanoscale plasmon-exciton systems, also known as plasmon-exciton polaritons, has been thoroughly investigated using transmission, reflection, and dark-field scattering spectroscopies. However, only a few recent studies performed experiments using photoluminescence spectroscopy on the individual hybrid nanostructure level. The latter is important for the detailed understanding of intrinsic excited state dynamics in strongly coupled systems. Here, we use correlative dark-field scattering (DF) and photoluminescence (PL) measurements to study polaritonic states in individual silver nanoprisms surrounded by molecular J-aggregates. We investigate these systems under various experimental conditions, including temperatures in the range T = 4-300 K, laser excitation wavelengths at 532, 568, and 640 nm, and a broad range of plasmon-exciton detunings. Our findings indicate that the lower energy peak in PL emission closely follows the lower polariton band observed in DF, while the higher energy PL peak follows the emission of uncoupled J-aggregate molecules and incoherent states. These observations further improve the understanding of excited state dynamics in strongly coupled plasmon-exciton systems. © 2019 American Chemical Society.